2019
DOI: 10.1093/cid/ciz141
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-finding Study of a Wild-type Influenza A(H3N2) Virus in a Healthy Volunteer Human Challenge Model

Abstract: Background The development of vaccines and therapeutics has relied on healthy volunteer influenza challenge studies. A validated human infection model with wild-type A(H1N1)pdm09 was reported previously. Our objective was to characterize a wild-type influenza A/Bethesda/MM1/H3N2 challenge virus in healthy volunteers. Methods Participants received a single dose of a cell-based, reverse-genetics, Good Manufacturing Practices–pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 33 publications
1
55
1
Order By: Relevance
“…Overall geometric mean HAI titers did increase after infection indicating exposure to the challenge virus. Titers remained low as has been observed before in human challenge models that screen participants for low HAI titers prior to challenge [32][33][34] , suggesting that screening for low HAI titer in challenge trials may select for a higher proportion of individuals than the 10-20% found in the general population that do not mount good antibody responses against the HA of influenza [35][36][37] . It is possible that these individuals may have a stronger cellular response to influenza than those who have a strong anti-HA head humoral response.…”
Section: Discussionmentioning
confidence: 65%
“…Overall geometric mean HAI titers did increase after infection indicating exposure to the challenge virus. Titers remained low as has been observed before in human challenge models that screen participants for low HAI titers prior to challenge [32][33][34] , suggesting that screening for low HAI titer in challenge trials may select for a higher proportion of individuals than the 10-20% found in the general population that do not mount good antibody responses against the HA of influenza [35][36][37] . It is possible that these individuals may have a stronger cellular response to influenza than those who have a strong anti-HA head humoral response.…”
Section: Discussionmentioning
confidence: 65%
“…After 2012, 2 influenza A strains were approved for use under an IND, with an initial goal of establishing an infectious dose that would cause mild to moderate disease in ≥60% of the volunteers. Those escalating dose-finding trials involved 46 volunteers over a 15-month period for an H1N1 virus and 37 volunteers over a 19-month period for an H3N2 virus [ 8 , 9 ]. Thus, the time needed to standardize a SARS-CoV2 infection model will be substantial.…”
mentioning
confidence: 99%
“…The limited access to the nose and oral cavity through use of the Studies addressing influenza have identified that both infectivity and the severity of an infection are dependent on the viral load to which a patient is exposed. 18,19 While this dose-dependence has not been specifically identified for SARS-CoV-2, eliminating or minimizing the inoculum of exposure is a reasonable goal for any aerosolized virus that has the potential for infection. Although there is currently no single strategy available to completely eradicate the risk of coronavirus transmission, methods to decrease dissemination such as the NPFS are likely to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Studies addressing influenza have identified that both infectivity and the severity of an infection are dependent on the viral load to which a patient is exposed 18,19 . While this dose‐dependence has not been specifically identified for SARS‐CoV‐2, eliminating or minimizing the inoculum of exposure is a reasonable goal for any aerosolized virus that has the potential for infection.…”
Section: Discussionmentioning
confidence: 99%